One-year evaluation of a new restorative glass ionomer cement for the restoration of non-carious cervical lesions in patients with systemic diseases: a randomized, clinical trial - Fatma Dilsad OZ; Ece MERAL; Esra ERGİN; Sevil GURGAN
Abstract Objective This randomized and clinical trial aimed to evaluate the performance of a new restorative Glass Ionomer Cement (GIC) for the restoration of non-carious cervical lesions (NCCLs) of patients with systemic diseases compared with a posterior resin composite after 12 months. Methodology 134 restorations were placed at 30 patients presenting systemic diseases by a single clinician. NCCLs were allocated to two groups according to restorative system used: a conventional restorative GIC [Fuji Bulk (GC, Tokyo Japan) (FB)] and a posterior resin composite [G-ænial Posterior (GC, Tokyo Japan) (GP)] used with a universal adhesive using etch&rinse mode. All restorative procedures were conducted according to manufacturer's instructions. Restorations were scored regarding retention, marginal discoloration, marginal adaptation, secondary caries, surface texture, and post-operative sensitivity using modified United States Public Health Service (USPHS) criteria after 1 week (baseline), 6, and 12 months. Descriptive statistics were performed using chi-square tests. Cochran Q and Mc Nemar's tests were used to detect differences over time. Results After 12 months, recall rate was 93% and the rates of cumulative retention failure for FB and GP were 4.9% and 1.6% respectively. Both groups presented similar alpha rates for marginal adaptation (FB 86.2%, GP 95.5%) and marginal discoloration (FB 93.8%, GP 97%) at 6-month recall, but FB restorations showed higher bravo scores than GP restorations for marginal adaptation and marginal discoloration after 12 months (p<0.05). Regarding surface texture, 2 FB restorations (3.1%) were scored as bravo after 6 months. All restorations were scored as alpha for secondary caries and postoperative sensitivity after 12 months. Conclusion Although the posterior resin composite demonstrated clinically higher alpha scores than the conventional GIC for marginal adaptation and discoloration, both materials successfully restored NCCLs at patients with systematic disease after a year. Clinical relevance Due to its acceptable clinical results, the tested conventional restorative GIC can be used for the restoration of NCCLs of patients with systemic diseases.